EFFECT OF STUNTING COUNSELING ON MATERNAL KNOWLEDGE AND ATTITUDES: A QUASI-EXPERIMENTAL STUDY - Riza Tsalatsatul Mufida; Nining Istigosah; Febrita Dwi Ratnasari (Universitas STRADA Indonesia, 2026)
Stunting is a global nutritional problem that affects children’s health and development, characterized by a height-for-age index below the standard growth reference. This study aimed to determine the effect of counseling on mothers’ knowledge and attitudes in handling stunted toddlers in Sumberejo Village, Kediri Regency. A quantitative pre-experimental design with a one-group pretest–posttest approach was employed. The study population consisted of all mothers of stunted toddlers in the village, totaling 36 respondents, who were included as research samples. Counseling on stunting served as the independent variable, while mothers’ knowledge and attitudes were the dependent variables. Data were collected using structured questionnaires and analyzed using the McNemar test. The results showed a significant improvement in mothers’ knowledge after counseling (p = 0.013), indicated by a decrease in low knowledge levels from 50% to 22%. However, no significant change was found in mothers’ attitudes (p = 0.754). In conclusion, counseling effectively improves maternal knowledge but has not significantly influenced attitudes toward stunting management, highlighting the need for continuous and comprehensive education programs.